The prison letters of Nelson Mandela - edited by Sahm Venter (New York Liveright Publishing Corporation, 2018)
While incarcerated in South Africa as a sentenced prisoner between 1962 and 1990, Nelson Mandela wrote hundreds of letters to loved ones, followers, prison authorities and government officials documenting his plight as the most prominent political prisoner of the twentieth century. Organised chronologically and divided by the four jails in which he was imprisoned, approximately 250 selected letters many of them never before seen by the public have been assembled here from the collections held by the Nelson Mandela Foundation, the South African National Archives and the Mandela family, amongst others, together with a foreword by Mandela's granddaughter.
Includes bibliographical references and index.
Keywords: Mandela, Nelson, 1918-2013--Correspondence.